Acute influenza virus-associated encephalitis and encephalopathy in adults: a challenging diagnosis. Issue 6 (December 2016) - Meijer, Wouter J.; Linn, Francisca H. H.; Wensing, Anne M. J.; Leavis, Helen L.; van Riel, Debby; GeurtsvanKessel, Corine H.; Wattjes, Mike P.; Murk, Jean-Luc
Abstract : Background : Acute influenza-associated encephalopathy/encephalitis (IAE) in adults is a rare but well-known complication of influenza virus infection. The diagnosis is difficult to make due to the absence of distinctive clinical symptoms and validated diagnostic criteria. We present an illustrative case and a case review on acute IAE in adults. Methods : We performed a Medline search of the English literature using the terms influenz*, encephal* and adult, and constructed a database of detailed descriptions of patients with influenza virus infection with influenza-like symptoms at the onset of neurological symptoms. Results : A total of 44 patients were included. Confusion and seizures were the most prevalent neurological symptoms, present in 12 (27 %) and 10 (23 %) patients, respectively. Magnetic resonance imaging (MRI) was performed in 21 patients and anomalies were found in 13 (62 %), with lesions located throughout the brain. Influenza virus RNA was detected in cerebrospinal fluid (CSF) in 5 (16 %) of 32 patients. Eight (18 %) of the forty-four patients died. The benefits of antiviral and immunomodulatory therapy have not been well studied. Discussion : Our results show that many different neurological symptoms can be present in patients with acute onset IAE. Therefore, the diagnosis should be considered in patients with fever and neurological symptoms, especially during the influenza season. Laboratory diagnosis consists of demonstration of influenza virus RNA in brain tissue, CSF or respiratory samples, and demonstration of intrathecal antibody production against influenza virus. The presence of brain lesions in MRI and influenza virus in CSF appear to be of prognostic value.